Pengaruh Pendidikan Karakter terhadap Motivasi Belajar di SD Negeri Sempu - Riyanto Riyanto; Rinesti Witasari (Institut Agama Islam Sunan Giri Ponorogo, 2022)
Character education plays an essential role in shaping students’ attitudes, behaviors, and learning motivation. This study aims to examine the influence of character education on students’ learning motivation at SD Negeri Sempu. The focus of the study includes the application of character values such as discipline, responsibility, honesty, and cooperation in daily learning activities. The findings indicate that consistent implementation of character education can enhance students’ intrinsic motivation, as reflected in their enthusiasm for participating in lessons, independence in completing assignments, and increased self-confidence. The study concludes that integrating character education into the teaching and learning process contributes positively to the improvement of students’ learning motivation.